Health care contact following a new incident neck or low back pain episode in the general population; the HUNT study. Issue 1 (December 2016) - Woodhouse, Astrid; Pape, Kristine; Romundstad, Pål; Vasseljen, Ottar
Abstract Background Low back and neck pain are commonly reported in the general population and represent frequent causes for health care consultations. The main aim of this study was to describe the determinants of health care contact during a 1-year period in a general population with recent onset spinal pain. Methods From 9056 participants in a general health survey in Norway we identified 219 persons reporting a recent onset (<1 month) of low back or neck pain. Questionnaires were given at 1 (baseline), 2, 3, 6 and 12 months after pain debut. The main outcome was self-reported health care contact due to spinal pain. Associations between health care contact and pain-related factors, other somatic and mental health factors, pain-related work limitations, physical activity and sociodemographic factors were explored. Results Conventional health care was sought by 93 persons (43 %) at least once throughout the year following the onset of pain. 18 persons (8 %) sought alternative health care only and 108 persons (49 %) sought no kind of health care. Baseline reports of coexisting low back and neck pain of equal intensity, poor self-reported health, symptoms of anxiety or depression, obesity and smoking were all associated with an increased tendency to seek conventional health care. Pain intensity and pain-related work limitations at each occasion were strongly associated with concurrent health care contact throughout the year. Higher education was associated with a reduced tendency to contact health care and no association was found for physical activity. Conclusion The main finding in this study was that people from the general population who seek health-care for a new incident of neck or low back pain report more symptoms of mental distress, poorer self-reported health and more intense pain with stronger work limitations compared to those who do not. The findings suggest that identification of complementary symptoms is highly relevant in the examination of spinal pain patients, even for those with recent onset of symptoms.